Conservation Genetics for Management of Threatened Plant and Animal Species - Ottewell, Kym; Byrne, Margaret (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on conservation genetic (and genomic) papers that demonstrate applied outcomes that inform practical threatened species management. We cover a broad range of species and genetic approaches, but focus on how conservation genetic information is used to underpin management actions for species recovery. Through the exposition of a diversity of approaches, we aim to demonstrate to conservation managers and researchers how conservation genetics can inform on-ground species management.